Forecasting Determination by Ousing Development Schedule Using Learning Machine Approach Using Clustering Method. (July 2019) - Allwin, M. S; Tanoto, Andi; Forbes,; Willy,; Ashari,
Abstract: Machine learning is a part of AI (Artificial Intelligence) which is a focus of development of system that can learn by "itself' without being reprogram many times by human. Machine Learning Application need a Data for a training subject before it produce an output. An Application like Machine Learning is usually in a specific domain or it couldn't be interpreted generally for all problems.Machine Learning does not mean without data. Which is means all Machine Learning Application needs Data for training material and to be analysed so it could produce an output. Before Machine Learning Application could work, it needs Data for training, the result of the training will be test with the same Data or the opposite data.The output of Machine learning usually come out as a prediction data with the trust worthy label. Clustering is grouping a data without based on some class data, moreover Clustering could be used for labelling a data in some class that haven't been known the type. Therefore Clustering is usually be categorized as unsupervised learning method.